PENGARUH FINANCING TO DEPOSIT RATIO(FDR) DAN NON PERFORMING FINANCING (NPF) TERHADAP RETURN ON ASSETS(ROA) PADA PT. BPRS AMANAH RABBANIAH PERIODE 2015-2018 - Aditya Achmad Fathony; Djodi Setiawan; Eneng Wulansari (Fakultas Ekonomi UNIBBA, 2021)
This study analyzes the description and influence of Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) on Return On Assets (ROA) at PT. BPRS Amanah Rabbaniah was compiled by Eneng Wulansari under the guidance of Mr. Aditya Achmad Fathony , SE., M.M., Ak., CA., CTA., A-CPA., MD. and Mr. Djodi Setiawan S.E., M.M., Ak., CA. This study aims to determine and explain how much influence the Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) have on Return On Assets (ROA) at PT. BPRS Amanah Rabbaniah 2015-2018 period. The analytical method used is descriptive and associative analysis with a quantitative approach to determine the description of each variable and multiple linear regression analysis to determine how much influence the two independent variables have on one dependent variable, which is then carried out by the t hypothesis test and F hypothesis test to see the level of significance. the effect. The population of this research is the quarterly financial reports of PT. BPRS Amanah Rabbaniah and samples were taken for 4 years, namely the 2015-2018 period. Based on the results of the analysis that simultaneously Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) have a significant effect on Return On Assets (ROA) with the coefficient of determination of 41% and the remaining 59% are other variables that also influence Return On Assets. (ROA) but not researched. Partially, Financing to Deposit Ratio (FDR) has no significant effect on Return On Assets (ROA) and Non Performing Financing (NPF) has a significant effect on Return On Assets (ROA). Keywords: Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) and Return On Assets (ROA) This study analyzes the description and influence of Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) on Return On Assets (ROA) at PT. BPRS Amanah Rabbaniah was compiled by Eneng Wulansari under the guidance of Mr. Aditya Achmad Fathony , SE., M.M., Ak., CA., CTA., A-CPA., MD. and Mr. Djodi Setiawan S.E., M.M., Ak., CA. This study aims to determine and explain how much influence the Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) have on Return On Assets (ROA) at PT. BPRS Amanah Rabbaniah 2015-2018 period. The analytical method used is descriptive and associative analysis with a quantitative approach to determine the description of each variable and multiple linear regression analysis to determine how much influence the two independent variables have on one dependent variable, which is then carried out by the t hypothesis test and F hypothesis test to see the level of significance. the effect. The population of this research is the quarterly financial reports of PT. BPRS Amanah Rabbaniah and samples were taken for 4 years, namely the 2015-2018 period. Based on the results of the analysis that simultaneously Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) have a significant effect on Return On Assets (ROA) with the coefficient of determination of 41% and the remaining 59% are other variables that also influence Return On Assets. (ROA) but not researched. Partially, Financing to Deposit Ratio (FDR) has no significant effect on Return On Assets (ROA) and Non Performing Financing (NPF) has a significant effect on Return On Assets (ROA).